Cooperative Learning: Investigating the Effect on Prospective Teachers’ Metacognitive Skills Development - Shahid Zulfiqar Ali, Muhammad; Asghar, Suneeta; Khan, Sohrab (Pakistan Languages and Humanities Review, 2022)
The current study was conducted to investigate the effect of the “Cooperative Learning enhanced with Metacognitive skills development strategy” on prospective teachers’ “Metacognitive skills”. The study was executed while using the Quasi-Experimental nonequivalent pretest-posttest control group design. The two sections of B. Ed (Honors) Semester-I (each consisting of 30 students) were selected conveniently for this study. One of them was considered as an experimental group whereas the other was a controlled group. These groups were taken from a public sector university based in Lahore. Before the intervention, both of the selected groups have been pretested and there was no statistical difference found among them concerning their Metacognitive Skills. The intervention (Cooperative Learning Enhanced with Metacognitive skills development strategy) was given to the experimental group whereas the controlled group received the conventional treatment. The intervention duration consisted of one semester only. The researcher used a performance test named “Metacognitive Skills Assessment Tool” (MSAT) was adapted, comprising 14 items (representing Metacognitive skills) to measure the prospective teachers’ skills. Furthermore, the Rubrics for Metacognitive Skills Assessment Tool (RMSAT) were used to rate the prospective teachers’ performance taken on MSAT. Descriptive Statistics (Mean Scores) and Inferential Statistics (Independent Sample t-test and Paired Sample t-test) were applied to the collected quantitative data. Base on the results, it has been revealed that the intervention have a significant effect on prospective teachers’ Metacognitive skills development. So, it is recommended that the teacher educators should use Metacognitive development strategies to develop these skills in prospective teachers.